Peluang Bisnis pada Jasa Kereta Api dan Pesawat Udara - Otok, Bambang Widjanarko; Suhartono, . (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2002)
The aim of this research is to study the application and comparison between models in time series analysis, particularly intervention, variation calendar and transfer function models. Intervention model is used to describe the effect of crisis that happened starting on July 1997 to the fluctuation of the number of train and plane passengers. Variation calendar model used in order to quantify and explain the effect of